‘When he comes into police custody, he has certain rights’: The burden for achieving access in a video-mediated interpreted custody interview - Skinner, Robert (International journal of police science & management, 2024)
This United Kingdom (UK)-based interdisciplinary proof-of-concept study explores the use of video remote interpreting (VRI) platforms to facilitate communication for deaf individuals using signed languages during their entry into Police Scotland's custody. The study employs three custody VRI simulations to assess the efficacy and limitations of VRI in this context. A unique framework is applied to scrutinise the management of equal access to routine police procedures, revealing disparities in the distribution of responsibility and highlighting the constrained capacity of interpreters. The research emphasises the need for law enforcement to move beyond mere interpreter provision – whether on-site or remote – and advocates for a holistic consideration of the overall experience of deaf people during police interactions. Furthermore, it underscores the imperative for interpreters to cultivate versatile skills, enabling them to address procedural and communication challenges, particularly when the welfare and safety of citizens are at stake. This investigation prompts a comprehensive re-evaluation of the support systems in place for deaf individuals in police custody, urging a shift towards a more inclusive and nuanced approach.